Cold Abscess of the Thigh in an Infant (Kathmandu University Medical Journal, 2014)
Local and minor adverse reactions to diphtheria–pertussis–tetanus (DPT) vaccination are usually mild and appear within 48 hours of vaccination. We herein report a rare association with intramuscular DPT injection and discuss pertinent issues. Primary tuberculous abscess was the final diagnosis. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11035 Kathmandu University Medical Journal Vol.11(1) 2013: 86-87